The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.eats.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Posterolateral Corner of the Knee With Achilles Tendon Allograft

Abstract: Posterolateral corner injuries of the knee are relatively rare; however, they can result in significant long-term disability without appropriate treatment. They often occur in the setting of multiligament knee injuries, and as a result, diagnosis and management can be challenging. Severe injuries often require reconstruction, and both anatomic and nonanatomic techniques exist. We describe our preferred operative technique to reconstruct the fibular collateral ligament and posterolateral corner using a single A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In the current literature, there are numerous surgical techniques that have been proposed for the reconstruction of all 3 key posterolateral structures (LCL, popliteus tendon [PT], and PFL) in order to restore the entire functional unit; however, outcome data from these studies are still highly variable. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 We prefer to use a combination of a Müller popliteal bypass for popliteus tendon and Larson figure-of-8 technique for LCL and popliteofibular reconstructions. 38 , 39 Grafts are secured to the lateral femoral epicondylar region with a screw and spiked washer to the anatomic insertion sites of the LCL and the popliteus tendon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, there are numerous surgical techniques that have been proposed for the reconstruction of all 3 key posterolateral structures (LCL, popliteus tendon [PT], and PFL) in order to restore the entire functional unit; however, outcome data from these studies are still highly variable. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 We prefer to use a combination of a Müller popliteal bypass for popliteus tendon and Larson figure-of-8 technique for LCL and popliteofibular reconstructions. 38 , 39 Grafts are secured to the lateral femoral epicondylar region with a screw and spiked washer to the anatomic insertion sites of the LCL and the popliteus tendon.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Numerous surgical protocols have been proposed for the treatment of these unusual injuries. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 In recent years, surgery of the major ligaments of the knee has evolved toward an anatomically oriented reconstruction. However, with evolving surgical techniques, additional problems developed, including tunnel convergence, either on the lateral or medial side of the knee, involving cruciate and collateral ligament reconstructions.…”
mentioning
confidence: 99%
“…Patients without asymmetry were treated with a one-tailed graft technique similar to that described by Arciero and later modified by Schechinger. 9,13,31 The anatomical one-tailed graft technique has been shown to provide good clinical outcomes with mean IKDC subjective scores and Lysholm scores exceeding 80 points. 9,32 We favor a one-tailed graft technique in the absence of an asymmetric hyperextension external rotation recurvatum deformity because it requires less surgical dissection, decreases graft burden, and reduces operative times while providing good functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For the recovery, the article underlined the importance of fixation in the fibular tunnel. In 2014, Kuzma et al 45) reported anatomic reconstruction of the PFL and LCL using the fibular-based technique and the Achilles tendon as an allograft. With this method, the reconstructed ligament can be repaired with the existing popliteus tendon.…”
Section: Treatmentmentioning
confidence: 99%